Productivity strategy in financial perspective of lq45 property company indonesia stock exchange - Katharina Priyatiningsih; Gilang Ramadhan (Faculty of Economics and Business Mulawarman University, 2022)
One of the strategies to achieve Long Term Shareholder Value through the company's financial perspective is to use a productivity strategy, in addition to a growth strategy. This productivity strategy is reflected in efforts to improve the cost structure and efforts to increase the use of assets, through product price, product quality, asset availability, asset functionality, and asset selection. The purpose of this study is to find out how the productivity strategy is carried out in the financial perspective of the five companies listed on the LQ45 index on the Indonesia Stock Exchange for the period February to July 2021. This research is a descriptive and associative research, with secondary data analysis through documentation, observation and interviews to primary data. The results showed that the productivity strategy in improving the cost structure was seen in the company's declining revenue performance even though the company still maintained the quality of its products. Meanwhile, the productivity strategy by increasing asset utility shows high asset availability, cooperation for asset functionality, and asset selection through deletion and acquisition. The conclusion of the productivity strategy is that it determines the company's financial performance in relation to stakeholders as a long-term investment consideration.